Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1093/humrep/dex319
|View full text |Cite
|
Sign up to set email alerts
|

Individualized versus standard FSH dosing in women starting IVF/ICSI: an RCT. Part 2: The predicted hyper responder

Abstract: 12 May 2011.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 29 publications
1
44
1
3
Order By: Relevance
“…For predicted hyper responders, several trials-including the OPTIMIST trial-indicated that an individualized FSH dose has no negative impact on LBR although it potentially reduces OHSS risks. 18,26,29 The results of the current analyses, however, suggest that those findings might not be generalizable to all women with a predicted hyper response. Reducing the FSH dose from 150 to 100 IU/d decreases OHSS risks for the majority of the predicted hyper responders.…”
Section: Clinical and Research Implicationscontrasting
confidence: 75%
See 3 more Smart Citations
“…For predicted hyper responders, several trials-including the OPTIMIST trial-indicated that an individualized FSH dose has no negative impact on LBR although it potentially reduces OHSS risks. 18,26,29 The results of the current analyses, however, suggest that those findings might not be generalizable to all women with a predicted hyper response. Reducing the FSH dose from 150 to 100 IU/d decreases OHSS risks for the majority of the predicted hyper responders.…”
Section: Clinical and Research Implicationscontrasting
confidence: 75%
“…A total of 234 predicted poor, 277 predicted suboptimal and 521 predicted hyper responders were randomly allocated to a standard FSH dose (150 IU/d) or an individualized dose (450, 225 or 100 IU/d, respectively) (Figure ). Table summarizes the baseline characteristics and first cycle outcomes . In the predicted poor and suboptimal responders, female age and body weight did not modify the effect of FSH dose individualization on the four pre‐specified outcomes (see Supporting Information, Table S1).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…COS compensates for inefficiencies in the following stages of the cycle such as oocyte maturation and insemination, embryo culture and transfer, and implantation (Fauser et al 1999). Even though the basis of COS involves the administration of gonadotropins (Macklon et al 2006), it is now very clear that a 'one-size-fits-all' approach does not exist and an individualized treatment approach can cater to a patient's unique characteristics and maximizes success, eliminates iatrogenic risks and minimizes the risk of cycle cancellation (Scott et al 2013a,b, La Marca & Sunkara 2014, Oudshoorn et al 2017, van Tilborg et al 2017a. On the other hand, PGT describes the procedure of removing one or more nuclei from embryos, blastomeres or trophectoderm cells, to test for mutations in gene sequence or aneuploidy before transfer selection (Practice Committee of Society for Assisted Reproductive Technology & Practice Committee of American Society for Reproductive Medicine (2008)).…”
Section: How Many Oocytes Do We Need?mentioning
confidence: 99%